Pheno-rhythmics of introduced woody plants, representatives of Syringa Genus - L. G. Dolgova; I. O. Zaitseva (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2005)
General nature of phenorhythms and peculiarities of phenophases of introduced lilacs, subject to their geographic origin and hydrothermal conditions, have been determined. Phenological development of most species includes all phenophases of vegetative and generative stages. Less stable species change dates and duration of phenophases, and reduce generative phases.